Synthesis and theoretical study of 5-phenyl-1,3,4-thiadiazole derivatives - Muğlu, Halit; Vurdu, Can Dogan; Sayiner, G.; Çavuş, M. Serdar; Kandemirli, Fatma; Ahmedzade, Misir (Mohammed Premier University jmaterenvironsci@gmail.com, 2015)
2-(ethyl xanthate) acetylamino-5-phenyl-1,3,4-thiadiazole, 2-(2-Hydroxybenal) amino-5-phenyl-1,3,4-thiadiazole, 2-(N-cylohexzyl carbamyl methylthiocarbamate)-5-phenyl-1,3,4- thiadiazole, 2-(Allyl) dithiocarbamate-5-phenyl-1,3,4-thiadiazole, dibenzyl-N-(5-phenyl-1,3,4-thiadiazole-2yl)dithiocarbamid, difenacyl-N- (5-phenyl-1,3,4-thiadiazole-2-yl) dithiocarbamid, 1,3-di(dithiocarbamate-5-phenyl-1,3,4-thiadiazole)propane were synthesized. The characterization of all new synthesized compounds was carried out by the 1H-NMR, IR, mass spectroscopic data and elemental analyses. The quantum chemical calculations were obtained by means of the DFT/6-311G(d,p) method. © 2015 Elsevier B.V., All rights reserved.
Keywords: DFT; IR; Thiadiazole; UV